2016
DOI: 10.1007/s10120-016-0640-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial disease status on lymph flow following gastrectomy in cases of carcinoma in the remnant stomach

Abstract: Purpose In cases of carcinoma in the remnant stomach (CRS), the lymphatic flow may be altered by the initial surgery. In this study of CRS after gastrectomy, we investigated how the regions of lymph node metastasis and changes in lymphatic flow depend on initial disease status. Method The study included 76 patients with CRS who underwent gastrectomy between September 2002 and November 2014. We analyzed and compared the clinicopathological factors and survival periods between patients after distal gastrectomy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…In the present study, operation interval from initial gastrectomy to surgery for RGC was significantly shorter in group M than in group B, which is consistent with that observed in previous studies (17,18). Although operation time was longer, the number of dissected LNs was significantly lower in group M, which was considered to be related to LN dissection of primary gastrectomy.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, operation interval from initial gastrectomy to surgery for RGC was significantly shorter in group M than in group B, which is consistent with that observed in previous studies (17,18). Although operation time was longer, the number of dissected LNs was significantly lower in group M, which was considered to be related to LN dissection of primary gastrectomy.…”
Section: Discussionsupporting
confidence: 93%
“…However, several studies have also shown that NG tumors have a very low potential to metastasize to the nodes along the G [12,14]. Such a metastatic tendency is expected to be preserved even in RGC at the NG, in which all lymphatic flow from the remnant stomach goes to the G [2]. The present study clearly demonstrated that the independent risk factors for nodal metastasis in the RGC were the tumor location, size and depth.…”
Section: Discussionsupporting
confidence: 66%
“…RGC is mostly limited to the upper third of the stomach. As the nodal station of the lesser curvature side is completely dissected at the primary surgery, all lymphatic flow from the remnant stomach reportedly travels to the greater curvature (G), regardless of the location [2]. Therefore, total gastrectomy with splenectomy is recommended for RGC [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic pathway in GSCs differs from that in the original stomach. In addition to the left gastric artery and posterior gastric artery in the normal stomach, an important lymphatic flow pathway exists along the anastomotic site and jejunum [30]. During the TG and SG procedures, the lymph nodes in the anastomotic jejunal mesentery or the duodenum were also removed.…”
Section: Discussionmentioning
confidence: 99%